Making law matter: projectivism and Hart's normativity - Swaminathan, S (2012)
This thesis explores a novel approach to understanding H.L.A.Hart's account of the 'normativity of law'. A successful account of the 'normativity of law' is meant to inter alia establish how legal requirements come to be morally binding. It will be argued that the internal point of view, key to Hart's account of normativity, can intelligibly constitute the 'source' of moral bindingness only if one assumes a projectivist model (resting on a non-cognitivist metaethic). The projectivist model understands moral bindingness as the motivational pull exerted by a moral judgment owing to the attitude of approval underlying it. Hart never expressly endorsed projectivism—far from it: he refused to take any firm metaethical stance at all. This thesis argues, however, that there are semantic and metaethical elements in Hart's scheme that naturally lend themselves to a projectivist model. A good portion of this thesis comprises in setting out, aligning—and where appropriate, emending—those elements so as to yield a coherent projectivist model of the 'normativity of law'. While discussing Hart's account of normativity occupies a bulk of this thesis, its overarching telos would be to take the first steps towards attempting a new begrundung of the projectivist model of 'normativity of law'. It does so by setting out the conceptual underpinnings of the projectivist model and by allaying some of the misgivings surrounding it. The projectivist model used to be prominent in the first half of the 20th century, thanks to the pioneering works of the Scandinavian Legal Realists, but has of late largely fallen into disrepute. Although Hart is widely credited with having taken apart the Scandinavian Legal Realists’ project—who themselves saw Hart’s project as contiguous with theirs—it will be argued that there is indeed a great deal convergence between the projects of Hart and the Scandinavian Legal Realists.